Community-based sustainable vector management strategies in rural areas of Zhejiang Province: criteria development and long-term impact assessment of vector control toward “Four Pest-Free Village” pilot program - Wang, Jinna; Xia, Jun; Zhang, Wenrong; Li, Tianqi; Luo, Mingyu; Liu, Qinmei; Guo, Junxiang; Sun, Jimin; Gong, Zhenyu; Jiang, Jianmin (Frontiers in Veterinary Science, 2025)
ObjectivesThis study aimed to develop the relevant criterion of pilot program of the “Four Pest-Free Village”(FPFV) and to further investigate the effects on vector control in Zhejiang Province.MethodsThe criterion of the FPFV was developed based on actual pilot experience and expert consultations. Vector density surveillance was conducted in all 11 prefecture-level cities of Zhejiang Province, including two FPFV and two control villages for each city. The CDC light trap method and Breteau Index (BI) method were used to monitor the density of mosquito. The fly trap method, night trapping method, and sticky board method were used to monitor the density of fly, rodent, and cockroach, respectively. Surveillance for mosquitoes and flies was conducted monthly from April to November 2023. Rodent and cockroach monitoring was conducted every odd month. Kruskal–Wallis test was used for data analysis.ResultsThe FPFV evaluation covered village organization management, health education, vector integrated control method, vector surveillance, and vector density control levels. A village could be named FPFV if the whole scored over 80 points. The Culex pipiens pallens (91.03%) was major species of mosquitoes; the total BI was 14.25; the Sarcophagidae (31.97%) and Musca domestica (31.41%) were major species of flies; the Rattus norvegicus (38.56%) was major species of rodents; the Blattella germanica (65.68%) was major species of cockroaches in rural areas of Zhejiang Province. All the vector densities investigated in the FPFV were lower than controls, including the adult mosquitoes (2.32 vs. 4.87 mosquitoes per trap-night), mosquito larvae (BI: 9.70 vs. 19.41), flies (1.32 vs. 2.17 flies per trap), rodents (0.41 vs. 0.84 rodents per 100 trap-nights), and cockroaches (the cockroach capture rate: 1.77% vs. 5.87%), and all the results were statistically significant (p ≤ 0.05).ConclusionThe findings from this study indicated that the FPFV was suitable for rural areas, and the method of sustainable vector management strategies was practical and reliable. Vector density in the FPFV could be controlled at a low level for a relatively long time than control village, which could greatly reduce the harassment of vector species on the population and the spread of related diseases.